Are land use options in viticulture and oliviculture in agreement with bioclimatic shifts in Portugal? - Andrade, Cristina (2021)
Land and climate are strongly connected through multiple interface processes and climate change may lead to significant changes in land use. In this study, high-resolution observational gridded datasets are used to assess modifications in the Köppen–Geiger and Worldwide Bioclimatic (WBCS) Classification Systems, from 1950–1979 to 1990–2019 in Portugal. A compound bioclimatic-shift exposure index (BSEI) is also defined to identify the most exposed regions to recent climatic changes. The temporal evolution of land cover with vineyards and olive groves between 1990 and 2018, as well as correlations with areas with bioclimatic shifts, are analyzed. Results show an increase of CSa Warm Mediterranean climate with hot summer of 18.1%, followed by a decrease in CSb (warm summer) climate of −17.8%. The WBCS Temperate areas also reveal a decrease of −5.11%. Arid and semi-arid ombrotypes areas increased, conversely humid to sub-humid ombrotypes decreased. Thermotypic horizons depict a shift towards warmer classes. BSEI highlights the most significant shifts in northwestern Portugal. Vineyards have been displaced towards regions that are either the coolest/humid, in the northwest, or the warmest/driest, in the south. For oliviculture, the general trend for a relative shift towards cool/humid areas suggests an attempt of the sector to adapt, despite the cover area growth in the south. As vineyards and olive groves in southern Portugal are commonly irrigated, options for the intensification of these crops in this region may threaten the already scarce water resources and challenge the future sustainability of these sectors